Precontinuity and applications - Janusz Matkowski (Annals of Mathematics and Physics - Peertechz Publications, 2022)
In this note, a map f acting between metric (or topological) spaces is referred to be pre-continuous at a point x if, for some sequence  of points  different from x and converging to x, the sequence  converges to  (section 2, Definition 1).